Association of breastfeeding, pacifier use, breathing pattern and malocclusions in preschoolers - Sebastião Batista Bueno; Telmo Oliveira Bittar; Fabiana de Lima Vazquez; Marcelo Castro Meneghim; Antonio Carlos Pereira (Dental Press Editora, 2013)
OBJECTIVE: To evaluate the association of breastfeeding duration, pacifier use and nasal air flow with occlusal disorders among children. METHODS: This cross-sectional observational study included 138 children aged 4 and 5 years selected in all the daycare centers of the city of Campo Limpo Paulista, Brazil. Questionnaires were applied to mothers to identify total duration of exclusive breastfeeding and non-nutritive sucking. The independent variables were: Sucking (pacifier, bottle, finger), breastfeeding duration and nasal air flow. The dependent variables were: Open bite, crossbite, overjet, overbite, diastema and maxillary deficiency. Frequency distribution calculations were performed, a chi-square test, the Fisher exact test and, after that, stepwise logistic regression were used for statistical analysis, and the level of significance was set at 5%. RESULTS: The use of a pacifier was the most deleterious factor and increased chances of having open bite in 33.3 times, marked overjet in 2.77 times and posterior crossbite in 5.26 times. CONCLUSION: There was a significant association between non-nutritive sucking, particularly the use of a pacifier, and occlusal disorders. These findings are important to plan the treatment of preschoolers. OBJETIVO: avaliar a associação do tempo de amamentação natural, tempo de uso de chupeta e aeração nasal em relação a problemas oclusais em crianças. MÉTODOS: foi realizado um estudo observacional transversal com universo de 138 crianças entre 4 e 5 anos, de creches de Campo Limpo Paulista/SP. Foram aplicados questionários às mães com o intuito de identificar o tempo de amamentação natural total e exclusiva e hábitos deletérios. Utilizaram-se as variáveis independentes hábitos deletérios (chupeta, mamadeira e dedo), tempo de amamentação natural e aeração nasal; e as variáveis dependentes mordida aberta, mordida cruzada, overjet, sobremordida, presença de diastema e atresia. Foram realizados cálculos das distribuições das frequências, teste de associação do qui-quadrado, exato de Fisher e, em seguida, regressão logística pelo método de stepwise, utilizando nível de significância de 5%. RESULTADOS: o uso de chupeta foi considerado o mais prejudicial dos hábitos deletérios, aumentando em 33,3 vezes a chance de mordida aberta; 2,77 vezes a chance de apresentar overjet acentuado e 5,26 vezes as chances de apresentar mordida cruzada posterior. CONCLUSÃO: houve uma forte associação entre hábitos deletérios (especialmente o tempo de uso de chupeta) e problemas oclusais, sendo esse fato importante no planejamento do tratamento de pacientes pré-escolares.